Pesan Moral dalam Film Tuhan Izinkan Aku Berdosa Karya Hanung Bramantyo (Prespektif Charles Sanders Pierce) - Riska Aulia; Nunu Burhanuddin (Institut Nalanda, 2026)
The film Tuhan Ijinkan Aku Berdosa is a religious drama film directed by Hanung Bramantyo. This film tells the story of a student named Nidah Kirani, or Kiran, who is depicted as an intelligent and devout woman who wants to dedicate her life to the path of God. However, Kiran is trapped in a strict religious group, until finally Kiran sues God for the various events she experiences. The purpose of this study is to determine the Moral Message in the Film Tuhan Ijinkan Aku Berdosa by Hanung Bramantyo (Charles Sanders Peirce's Perspective). The method used is library research with a qualitative approach. Data were collected through observation of film scenes relevant to the moral message, and supported by secondary sources such as books, journals, and articles. Data analysis was carried out using Charles Sanders Peirce's semiotic approach using icons, indexes, and symbols. The results of the study show that this film contains ten moral messages, both explicit and implicit. These messages include dhikr (remembrance of God), seeking forgiveness (istighfar), and awareness of faith, regret for sins, sharing, praying for the deceased, husnuzon (having good thoughts) toward Allah, asking for forgiveness, empathy, critical thinking, and advice. The messages contained in this film are inseparable from the concept of amar ma'ruf nahi munkar (enjoining good and forbidding evil). Thus, it can be concluded that this film serves not only as a medium of entertainment but also as a means of conveying moral and spiritual values ​​relevant to society.